(3EOGQI bfhGJ GdJhRjY (B/s - (3GdVehQ, gGfj MGeOs ((3YeGf(B: s (3OGQ hGFd ddfTQ h GdJhRjY(B, s, 2002)
(3eGgjI GdbfhGJ GdJShjbjI hJNWjWgG h JMdjd HjFI GdbfGI GdJShjbjI eY JfGhd GdeDSSGJ GdhXGFajI (B: (3GdSeGSQI h GdhcdGA h GdeDSSGJ GdJLGQjI (B: (3efTBJ JLGQI GdLedI h GdeDSSGJ GdJLGQjI (B: (3efTBJ JLGQI GdJLRFI h cPG GdJWQb Gdi GdbjGOI OGNd GdbfGI GdJShjbjI h EOGQI GdUQGY OGNd bfhGJ GdJShjb h Jbjje COGA gPg GdbfhGJ ceG Je JfGhd EOGQI GdbfhGJ GdJShjbjI h GdeRjL GdJShjbj h EOGQI GdJhRjY GdeGOj h h GNjQG bfhGJ JShjb GdNOeGJ h bfhGJ GdJShjb GdOhdjI(B.s
(3GdeQGLY U(B.440s
Keywords: (3EOGQI GdJShjbs; (3GdJhRjYs